(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Now a day Cloud Computing plays an important role in business environment. Cloud computing is the on-demand availability of computer system resources, especially data storage in computer system. Cloud computing is the delivery of computing services including servers, storage, data, databases, networking, software, analytics, and intelligence over the Internet. Now a day we are using cloud computing in different types of business, any organization like manufacturing industry,E-Commerce as well as for our personal use. If we want to use an online service such as send e-mail, edit documents, edit images, edit videos, watch movies or TV, listen music, play video games, or store pictures, images and other files, it’s likely that cloud computing is making it all possible behind the tasks. With help of Cloud computing we can store and protect the data easily till long period. According to a study by the International Data Group, 70% of businesses are already using the technology i.e. Cloud computing, and 18% say they plan to implement cloud-computing solutions at some point.